Underwater Drones as a Low-Cost, yet Powerful Tool for Underwater Archaeological Mapping: Case Studies from the Mediterranean - Eleni Diamanti; Øyvind Ødegård; Vasilis Mentogiannis; George Koutsouflakis (Journal of Computer Applications in Archaeology)
This paper investigates the transformative impact of micro-class Remote Operated Vehicles (ROVs), commonly known as underwater drones, on underwater archaeological mapping. With advancements in Unmanned Underwater Vehicles (UUVs) technology leading to increased capabilities and reduced costs, these compact and user-friendly drones are making underwater archaeological sites more accessible, reducing the need for human diving. The paper first highlights the advantages of ROVs, including their portability, maneuverability, and ability to perform semi-autonomous mapping with real-time data assessment, which enhances decision making and minimizes the need for site revisits. Second, it presents two case studies from the Phournoi archipelago in Greece, demonstrating the effective use of underwater drones in the photogrammetric mapping of a Late Roman shipwreck of amphora cargo, as well as the large-scale surveying of a historically significant anchorage site. The findings underscore the potential of this technology to revolutionize underwater archaeological documentation, akin to how terrestrial cultural heritage mapping has been highly benefited from aerial drone photogrammetry.